THE EFFECT OF LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN PT ISS INDONESIA CLEANING SERVICE DIVISION SOUTH JAKARTA - Iis Noviyanti; Juwita Ramadani Fitria; Lia Asmalah (Yayasan Education and Social Center, 2022)
This study aims to determine how leadership on employee performance at PT. ISS Indonesia Cleaning Service Division Placement of PT. Jakarta Land - South Jakarta. To find out how work motivation on performance at PT. ISS Indonesia Cleaning Service Division Placement of PT. Jakarta Land - South Jakarta. to find out how leadership and influence of work motivation on employee performance at PT. ISS Indonesia Cleaning Service Division Placement of PT. Jakarta Land - South Jakarta. This research method uses a quantitative descriptive method. This research provides an overview of the data to determine the relationship between the independent and dependent variables. The sampling technique used is proportional random sampling using the saturated sampling technique. The data collection technique in this research is using observation and questionnaires. The data was obtained by a questionnaire with as many as 61 employees. The questionnaire data were analyzed using the SPSS version 26 calculation, the correlation coefficient test method, the multiple linear regression test, the coefficient of determination, and the significant hypothesis test at a = 5%. The results of this study are that leadership has a significant effect on employee performance with the regression equation Y = 18.162 + 0.543X1. The correlation coefficient value is 0.627, meaning that the two variables have a strong level of relationship with a determination coefficient of 39.3%. Hypothesis test obtained t count> t table or (6.187> 2,001). Thus, H0 is rejected, and H1 is accepted, meaning a significant influence between leadership and employee performance. Work motivation significantly affects employee performance with the regression equation Y = 20.768 + 0.472X2. The correlation coefficient value is 0.536, meaning that both have a strong relationship level with a determination coefficient of 28.7%. Hypothesis test obtained t count> t table or (4.8721> 2,001). Thus, H0 is rejected, and H2 is accepted, meaning a significant influence between work motivation and employee performance. Leadership and work motivation have a significant effect on employee performance with the regression equation Y = 13,694 + 0,413X1 + 0,244X2. The correlation coefficient value obtained is 0.669, meaning that the independent variable with the dependent variable has a strong level of relationship with the coefficient of determination or influence simultaneously of 44.8%. In comparison, the remaining 55.2% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (23,516> 2,760). Thus H0 is rejected, and H3 is accepted. This result means a significant influence simultaneously between leadership and work motivation on employee performance at PT. ISS Indonesia Cleaning Service Division Placement of PT. Jakarta Land - South Jakarta